Evaluation of Bone Morphogenetic Protein-4 gene polymorphism for growth traits in Indian goat breeds - KHARE, VAISHALI; JOSHI, SHRIKANT; THAKUR, MOHAN SINGH; SINGH, AJIT PRATAP; VANDRE, RAJESH (The Indian Journal of Animal Sciences, 2022)
The genetic improvement of production traits can be made through marker assisted selection using a candidategene approach. Bone morphogenetic proteins (BMPs) are multifunctional growth factors that belong to thetransforming growth factor b (TGF-b) superfamily. This study aimed to detect the genetic polymorphism of BMP-4in different goat breeds by polymerase chain reaction-single strand confirmational polymorphism (PCR-SSCP) andassociation of polymorphic variants with growth traits. The amplified fragments of BMP4 gene of 380 bp size wereanalysed using SSCP in non-denaturing PAGE and the results showed the presence of two genotypes: AA (47-67%) and BB (33-53%) in Barbari, Sirohi and Black Bengal breed. The association of BMP-4 polymorphism withdifferent growth trait parameters showed non-significant effect of genotypes. However, some genotypes showednon-significant superiority over others. Further research on a large population is required to validate the role of theBMP-4 gene in goat growth traits.